2016
DOI: 10.1186/s12917-016-0784-7
|View full text |Cite
|
Sign up to set email alerts
|

Has intravenous lidocaine improved the outcome in horses following surgical management of small intestinal lesions in a UK hospital population?

Abstract: BackgroundPerioperative lidocaine treatment is commonly used in horses that undergo surgical treatment of colic, to prevent or treat postoperative ileus and reduce the effects of intestinal ischaemia-reperfusion injury. However, its clinical efficacy has not been evaluated in a large population of horses undergoing small intestinal surgery. The aim of the current study was to evaluate whether systemic lidocaine administration reduced the prevalence, volume and duration of postoperative reflux and improved rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…1.3 mg/kg in 500 ml NaCl for a 30 min infusion) also promotes gastrointestinal motility by suppressing local sympathetic nerves (Malone et al 2006, Okamura et al 2009). However, a recent study showed that lidocaine therapy had no effect on the prevalence of postoperative reflux (Salem et al 2016). Side effects include fasciculations and collapse (Malone et al 2006, Okamura et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…1.3 mg/kg in 500 ml NaCl for a 30 min infusion) also promotes gastrointestinal motility by suppressing local sympathetic nerves (Malone et al 2006, Okamura et al 2009). However, a recent study showed that lidocaine therapy had no effect on the prevalence of postoperative reflux (Salem et al 2016). Side effects include fasciculations and collapse (Malone et al 2006, Okamura et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Also, this increased rate of POR was noted recently in a report from a single hospital over a 10‐year span and an explanation could not be offered (Salem et al . ). Granted, more specific inclusion criteria and improvements in record keeping could explain this apparent trend ( Fig ), but the role of surgery and related effects on intestinal function ( Fig ) warrant close consideration.…”
Section: Prevalence Of Pormentioning
confidence: 97%
“…A more recent study demonstrated that lidocaine did not affect the prevalence of post‐operative reflux, total reflux volume, duration of reflux and post‐operative survival after small intestinal surgery (Salem et al . ). That lidocaine has anti‐inflammatory effects in equine small intestine is unlikely (Cook ; Grosche et al .…”
Section: Lidocainementioning
confidence: 97%
See 1 more Smart Citation
“…); however, a more recent study found no effect of lidocaine administration on total reflux volume or duration, or on post‐operative survival (Salem et al . ).…”
Section: Systemic Analgesicsmentioning
confidence: 97%